Increased Interest among Malaysian Technical Students with Different Learning Styles - Azyani A. Jalil, Noor; Iman Kassim, Nurul; Rizal Madar, Ahmad (International Journal of Psychosocial Rehabilitation, 2019)
Learning style is an important concept and needs to be focused on education as it is a key factor in shaping an individual’s quality. Every individual has different learning styles. The learning process of students will be practiced directly through their learning style. This study used a quasi-experimental design with pre-post-test groups of unbalanced groups. The study sample was selected to carry out this study using the purposive sampling method. The students involved in this study were from Polytechnic Merlimau, Malacca, and Polytechnic Port Dickson, Negeri Sembilan. The findings show that students who are flipped learning experience a 97.9% increase in interest. In addition, the mean of the treatment group was 102.43 and the mean of the control group was 60.59. Active dimension students showed mean values of 82.26 and reflective dimension students mean 80.67. On the whole, students who engage in flipped learning tend to experience increased interest despite having active and reflective dimensions. In conclusion, students’ interest in the subject of Electrical Technology 1 can be enhanced if students are aware of their own learning style. Accordingly, this method of flipped learning is proposed to be applied by the lecturers during the learning and teaching process to enhance the interest of students, especially technical students in polytechnic Malaysia.